Economic sustainability of extending lay cycle in the supply-managed Canadian egg industry - Traore, Ousmane Z.; Doyon, Maurice (Frontiers in Animal Science, 2023)
The Canadian egg industry has increased its performance over the years, including hen productivity and feed conversion efficiency. Moreover, genetic improvements combined with improved feed and light management have recently resulted in hens that can technically produce 500 eggs in an 80 week laying cycle. Nevertheless, most egg farms in Canada are still on a 51-week production cycle despite high hen productivity at culling. Lack of economic impact information, combined with the fact that egg production is under supply management in Canada and that farmers are paid their cost of production reduces the incentive to extend laying cycles despite savings associated with lower rates of flock replacement. On the other hand, a greater percentage of large eggs is beneficial to the value chain while fewer resources used per eggs associated with longer laying cycles generate environmental benefits. This paper analyzes the economic sustainability of extending laying cycles in Canada by combining partial budgeting analysis based on farms level data with a nonlinear mathematical programming model to assess the economic costs and benefits of extending laying cycles, while taking into consideration the policy context of supply management in Canada. Results suggest that for hens housed in an aviary, extending the laying cycles from 51 to 64 weeks would improve profits by roughly 6% per year over a 5-year period. Our optimization model, forecast that a laying cycle of 71 weeks would be economically optimal with an average productivity of 6.7 eggs per hen per week and a cumulative mortality rate of 5.53%. This paper, through an innovative methodologically approach that combines partial budgeting and nonlinear mathematical programming models, generates information to help the egg industry stakeholders to make informed decisions on extending laying cycles while considering the policy context of supply management in Canada.